A informação dos telecentros do Vale do Jequitinhonha como aporte ao desenvolvimento social dos distritos de São Gonçalo do Rio das Pedras e Milho Verde em Minas Gerais - Marina Cajaiba da Silva (2005)
This study delineates the globalized context of the present time, where Information and Communications Technologies (ICTs) can be understood as opportunities of citizenship for excluded groups who find themselves at the margins of local and global human development in the era of information, such as the communities in the districts of São Gonçalo do Rio das Pedras and Milho Verde in the Vale do Jequitinhonha, Minas Gerais one of the poorest regions in the country. As a major goal, this study intended to identify how information originating from the telecenters of the Rede Rural de Telecentros Comunitários, of the NGO Gemas da Terra, has contributed to the social inclusion of these communities; to analyze the project for installing a telecenter for the communities studied; to verify any actions aimed at the integration of those who attend the telecenters with the other people of the community, to prevent a possible concentration of opinions and alienation between the two groups; and to point out results of the actions undertaken by the communities and their consequent practical influence on the daily life of local society. The methodology includes a document analysis of the Guia Gemas da Terra de Telecentros Rurais, non-participant observation at the telecenters, and semi-structured interviews with the users, volunteers, and representatives of the community organizations of the regions studied, where the dissemination and the use of the ICTs have been regarded by the communities as important supporters for improving conditions of life of the population by increasing opportunities for information, work, income, education, and leisure. Among the conclusions reached by this study, it was noted that the greatest social contribution of the pilot project of the NGO Gemas da Terra was to show the communities involved in the project the potential that the Internet offers to these districts, especially to the common people. Nevertheless, from the results obtained by this study, it became evident that the long way to be covered by informational inclusion toward the effective contribution of social questions in marginalized and integrated groups in the information era, was not totally explicit in the area studied.